Reading comprehension strategies: instruction and assessment in elementary school - Gutierrez-Braojos, Calixto; Salmerón Pérez, Honorio (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
Literacy skill is one of the most important psychological tools in both learning and teaching processes. Its transversal character carries positive or negative collateral effects on other academic areas. In the recent decades, the role of learning strategies has been emphasized as important psychological tools that facilitate students to achieve reader skills. In this text, we define learning strategies that facilitate the reading process and comprehension in elementary school and firsts grade students. Furthermore, we discuss intervention programs, techniques and assessment tools that might be useful in different educational levels.